Women’s Role in Buying Behaviour for Durables: A Study of Malwa Region in Punjab - Rani, Malika (Indian Journal of Marketing, 2012)
This paper analyzed the role of women in buying behavior for durables. As far as the present scenario is concerned, the employment participation of women grew to 31 percent in 2005 from 26 percent in 2000, the first rise seen in the decade. The all India Census recorded that female headed households rose to 12 percent in 2001 from the roughly 9 percent a decade ago. The average age of marriage is still young, at just less than 20 years from 17.1 years in 1971. In this study, the questionnaire method was used to collect the data. A sample of 200 women was drawn by using convenient sampling from 4 Districts (Patiala, Ludhiana, Ferozepur & Moga) of Malwa region in Punjab. The study applied the Anova technique to know whether there is any relation between the demographic factors (age & occupation) & buying behavior for durables (car & washing machine). The findings of the study revealed that at the final purchase decision stage for cars, only 10% women dominated the decision making process. As washing machines are mainly used by women, for washing machines, 44% of the women dominated the decision making process.